Method for producing composition, and method for producing ophthalmic lens
By heating at a mixture of the double siliconoxane and metal oxide particles that contain cationic aggregate groups exceeding 60 ° C, and mix with cation aggregates. Hardness solves the problem of insufficient scratch resistance in plastic lenses in existing technologies.
Patent Information
- Application Number
- CN202380047358.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-29
- Filing Date
- 2023-06-27
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art When imparting abrasion resistance to a plastic eyeglass substrate, it is difficult to effectively control the viscosity change of the composition and the hardness of the cured film.
By heat-treating a mixture containing silsesquioxane and metal oxide particles having a cationic polymerizable group at a temperature exceeding 60°C, the viscosity change during storage of the composition is suppressed, and the mixture is combined with a cationic polymerization initiator. Mix to make composition.
It is realized that the viscosity of the composition changes little with time, and the hardness (especially scratch hardness) of the cured film obtained using this composition is excellent.
Smart Images

Figure SMS_2 
Figure SMS_4 
Figure SMS_13
Abstract
Description
Technical Field
[0001] The present disclosure relates to a method for producing a composition and a method for producing an ophthalmic lens. Background Art
[0002] In order to impart scratch resistance to a plastic eyeglass lens substrate, a hard coating layer may be disposed on the plastic eyeglass lens substrate (for example, Patent Document 1).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application No. 2010-515778 Summary of the invention
[0006] The present disclosure relates to a method for producing a composition, comprising: step 1 of heating a mixture containing silsesquioxane having a cationically polymerizable group and metal oxide particles at a temperature exceeding 60° C.; and step 2 of mixing the mixture obtained in step 1 with a cationic polymerization initiator to produce a composition. DETAILED DESCRIPTION
[0007] Hereinafter, the method for producing the composition of the present disclosure will be described in detail.
[0008] In the composition, it is desirable that the change in viscosity over time is small from the viewpoint of workability. In addition, it is desirable that the hardness of a cured film formed using the composition is excellent from the viewpoint of application to hard coatings and the like.
[0009] The composition produced by the method for producing a composition of the present disclosure has a small change in viscosity over time, and a cured film obtained using the composition is excellent in hardness (particularly scratch hardness).
[0010] Hereinafter, the method for producing the composition according to the present embodiment will be described in detail.
[0011] In addition, in this specification, "to" is used to mean that the numerical values described before and after it are included as a lower limit and an upper limit.
[0012] [Method for producing composition]
[0013] The method for producing the composition according to the present embodiment is a method comprising step 1 and step 2.
[0014] The step 1 is a step of heating a mixture containing silsesquioxane having a cationically polymerizable group and metal oxide particles at a temperature exceeding 60° C. The step 2 is a step of mixing the mixture obtained in the step 1 with a cationic polymerization initiator to produce a composition.
[0015] As described later, by performing the heat treatment in step 1 before the above step 2, a change in viscosity of the composition during storage can be suppressed.
[0016] In addition, the composition produced by the method for producing a composition of the present disclosure contains silsesquioxane having a cationically polymerizable group and metal oxide particles, and thus has excellent scratch hardness.
[0017] Hereinafter, each step in the method for producing the composition according to the present embodiment will be described in detail.
[0018] <Process 1>
[0019] Step 1 is a step of heating a mixture containing silsesquioxane having a cationically polymerizable group and metal oxide particles at a temperature exceeding 60° C. When step 1 is performed, it is presumed that polymerization of the cationically polymerizable group of silsesquioxane proceeds due to a trace amount of acid from the metal oxide particles, and a portion of the silsesquioxane is prepolymerized.
[0020] Hereinafter, first, the materials used in step 1 will be described in detail, and then the steps of the step will be described in detail.
[0021] (Silsesquioxane having a cationically polymerizable group)
[0022] In the above step 1, silsesquioxane having a cationically polymerizable group (hereinafter also simply referred to as “specific silsesquioxane”) is used.
[0023] Generally, silsesquioxane is a silane compound having a basic skeleton represented by formula (1) obtained by hydrolyzing a trifunctional silane compound such as alkoxysilane, chlorosilane and silanol. As the structure of silsesquioxane, in addition to the irregular form called random structure, a ladder structure, a cage structure (completely condensed cage structure) and an incomplete cage structure (a partially cleaved structure of the cage structure, a structure in which a part of silicon atoms is missing from the cage structure or a structure in which a part of silicon-oxygen bonds of the cage structure are cut) are also known.
[0024] In the following formula (1), R 3 Represents an organic group.
[0025] Formula (1) R 3 -SiO 3 / 2
[0026] The specific silsesquioxane preferably has R in the formula (1): 3 It is a basic skeleton of an organic group having a cationically polymerizable group.
[0027] The structure of the specific silsesquioxane is not particularly limited, and may be any of the above-mentioned random structure, ladder structure, cage structure, and incomplete cage structure, or may be a mixture of a plurality of structures.
[0028] The cationically polymerizable group equivalent in the specific silsesquioxane is not particularly limited, but is preferably 50 to 500 g / eq., more preferably 150 to 300 g / eq., from the viewpoint of obtaining a better hardness of a cured film formed using the composition.
[0029] The cationically polymerizable group in the specific silsesquioxane is not particularly limited, and examples thereof include an oxetanyl group and an epoxy group.
[0030] The oxetanyl group is a group represented by the following formula (2). 2 represents a hydrogen atom or an alkyl group (for example, methyl, ethyl, propyl, etc.). Indicates the bonding position.
[0031]
[0032] The epoxy group is a group represented by the following formula (3). 1 represents a hydrogen atom or an alkyl group (for example, methyl, ethyl, propyl, etc.). Indicates the bonding position.
[0033]
[0034] The specific silsesquioxane may be synthesized by a known method, or a commercial product may be used. Examples of the commercial product include OX-SQ TX-100, OX-SQ SI-20, OX-SQ HDX, and OX-SQ ME-20 manufactured by Toagosei Co., Ltd.
[0035] (Metal oxide particles)
[0036] In the above step 1, metal oxide particles are used.
[0037] The type of metal oxide particles is not particularly limited, and known metal oxide particles can be listed. As metal oxide particles, for example, oxide particles of at least one metal selected from Si, Al, Sn, Sb, Ta, Ce, La, Fe, Zn, W, Zr, In and Ti can be listed. Among them, from the perspective of operability, the metal oxide particles are preferably oxide particles containing Si (silicon oxide particles), oxide particles containing Sn (tin oxide particles), oxide particles containing Zr (zirconium oxide particles) or oxide particles containing Ti (titanium oxide particles). That is, it is preferred that the metal oxide particles contain at least one atom selected from the group consisting of Si, Sn, Zr and Ti.
[0038] In addition, the metal oxide particles may contain only one type of the metals (metal atoms) exemplified above, or may contain two or more types of metals (metal atoms).
[0039] The average particle size of the metal oxide particles is not particularly limited, but is preferably 1 to 200 nm, more preferably 5 to 30 nm. Within the above range, the dispersion stability of the metal oxide particles in the composition is better, and whitening of the cured product can be further suppressed.
[0040] The average particle size is determined by measuring the diameters of 100 or more metal oxide particles using a transmission microscope and averaging the diameters. When the metal oxide particles are not perfectly circular, the major diameter is used as the diameter.
[0041] The metal oxide particles can be used in a colloidal state dispersed in a solvent. For example, when the metal oxide particles contain Si as a metal, they may be colloidal silica.
[0042] When colloidal silica is used as the metal oxide particles, examples of commercially available products include: OSCAL series manufactured by JGC Catalysts & Chemicals, Ltd., SNOWTEX series manufactured by Nissan Chemical Industries, Ltd., and Quartron series manufactured by Fuso Chemical Industries, Ltd.
[0043] In step 1, other components besides the above-mentioned specific silsesquioxane and metal oxide particles may be used.
[0044] (Solvent)
[0045] A solvent may be used in the above step 1. The solvent here may be the solvent added in the step 1, and when metal oxide particles commercially available in the form of a colloidal solution are used, the solvent may be the dispersion medium thereof.
[0046] The solvent is not particularly limited and may be water or an organic solvent.
[0047] Examples of the organic solvent include alcohol solvents, ketone solvents, ether solvents, ester solvents, hydrocarbon solvents, halogenated hydrocarbon solvents, amide solvents, sulfone solvents, and sulfoxide solvents.
[0048] The alcohol solvent is preferably an alcohol solvent having 10 or less carbon atoms, and more preferably an alcohol solvent having 5 or less carbon atoms (eg, isopropyl alcohol). The alcohol solvent may be a polyol having two or more hydroxyl groups in one molecule.
[0049] Examples of other components, in addition to the above-mentioned solvents, include ultraviolet absorbers, surfactants, polymerization inhibitors, antioxidants, coating film conditioners, light stabilizers, antioxidants, anti-coloring agents, dyes, fillers, and internal mold release agents.
[0050] (Steps of process 1)
[0051] In the above step 1, the mixture containing the specific silsesquioxane and the metal oxide particles is heated at a temperature exceeding 60°C.
[0052] The method for obtaining the mixture containing the specific silsesquioxane and the metal oxide particles is not particularly limited, and the components may be mixed all at once or added and mixed in portions.
[0053] After obtaining the above mixture, stirring treatment may be performed as required.
[0054] The mixing ratio of the specific silsesquioxane and the metal oxide particles in the mixture is not particularly limited, and the mass ratio of the content of the metal oxide particles to the content of the specific silsesquioxane in the mixture is preferably 0.2 to 10.0, more preferably 0.5 to 2.0.
[0055] The total content of the specific silsesquioxane and the metal oxide particles in the mixture is not particularly limited, but is preferably 80 to 100% by mass, more preferably 90 to 100% by mass, based on the total solid content in the mixture.
[0056] It should be noted that the solid content in the mixture refers to the components other than the solvent in the mixture. It should be noted that even if the component is in a liquid state, it is calculated as a solid content.
[0057] As described above, the mixture may contain other components besides the specific silsesquioxane and the metal oxide particles.
[0058] As other components, the above-mentioned solvents can be mentioned.
[0059] The content of the solvent in the mixture is not particularly limited, but is preferably 30 to 60% by mass, more preferably 40 to 60% by mass, based on the total mass of the mixture.
[0060] The method for heating the mixture in step 1 is not particularly limited, and a known method may be used, and a method using a known heating device may be used.
[0061] Examples of the heating device include a hot plate, an electric heater such as a hooded heater, an infrared heater, an oil bath such as an oil bath, and a hot water bath such as a water bath.
[0062] The heating may be performed in an open system or in a closed system, but is preferably performed in a closed system because the temperature of the mixture can be raised to a temperature higher than the boiling point of the solvent in the mixture and the mixture can be heated at a high temperature even in the presence of volatile components contained in the mixture.
[0063] Furthermore, during heating, stirring treatment may be performed as necessary.
[0064] The heating temperature of the mixture is higher than 60°C, preferably 80°C or higher, more preferably 100°C or higher, further preferably 120°C or higher, particularly preferably 140°C or higher.
[0065] In addition, the upper limit of the heating temperature is not particularly limited, but is preferably 200° C. or lower.
[0066] It should be noted that the above-mentioned heating temperature refers to the set temperature of the heating device (hot plate etc.) used when heating the above-mentioned mixture.
[0067] The heating time of the mixture may be appropriately selected according to the above-mentioned heating temperature and is not particularly limited, but is, for example, preferably 1 hour or more, more preferably 3 hours or more, further preferably 4 hours or more, and particularly preferably more than 4 hours.
[0068] The upper limit of the heating time is, for example, preferably 12 hours or less, more preferably 10 hours or less, further preferably 8 hours or less, particularly preferably less than 8 hours, and most preferably 7 hours or less.
[0069] <Process 2>
[0070] Step 2 is a step of mixing the mixture obtained in the above-mentioned step 1 with a cationic polymerization initiator to produce a composition.
[0071] Hereinafter, first, the materials used in step 2 will be described in detail, and then the steps of the step will be described in detail.
[0072] (Cationic polymerization initiator)
[0073] In the above step 2, a cationic polymerization initiator is used.
[0074] The cationic polymerization initiator is not particularly limited, and examples thereof include thermal cationic polymerization initiators and photocationic polymerization initiators.
[0075] The type of thermal cationic polymerization initiator is not particularly limited, and known thermal cationic polymerization initiators can be cited. Examples of thermal cationic polymerization initiators include sulfonium salts, aniline salts, pyridine salt, toluidine salt, Salt and iodine Salt, etc. Salt. It should be noted that these The salt contains hexafluorophosphate anion (PF6 - ), tetrafluoroborate anion (BF4 - ), hexafluoroantimonate anion (SbF6 - ) and hexafluoroarsenate anion (AsF6 - ) and other anions.
[0076] The sulfonium cation may be a triarylsulfonium cation. Examples of the triarylsulfonium cation include a triphenylsulfonium cation in which the aryl group is a substituted phenyl group having an alkyl group, a thioether group, an alkoxy group or the like as a substituent.
[0077] Specific examples of the triarylsulfonium cation include a diphenyl[4-(phenylthio)phenyl]sulfonium cation, a triphenylsulfonium cation, and an alkyltriphenylsulfonium cation.
[0078] Examples of commercially available products of the thermal cationic polymerization initiator include ADEKA OPTORON CP-66 manufactured by ADEKA Corporation and SAN-AID SI-150L manufactured by Sanshin Chemical Industries, Ltd.
[0079] The type of photocationic polymerization initiator is not particularly limited, and known photocationic polymerization initiators can be cited. Examples of photocationic polymerization initiators include iodine Salts (such as aromatic iodine onium salts) and sulfonium salts (e.g. aromatic sulfonium salts) The photocationic polymerization initiator is preferably an aromatic sulfonium salt, such as an onium salt, a halogen-containing compound such as a s-triazine derivative, a sulfone compound, a sulfone acid compound, a sulfonimide compound, and a diazomethane compound. Among them, from the viewpoint of curability, the photocationic polymerization initiator is preferably an aromatic sulfonium salt.
[0080] (Other ingredients)
[0081] In step 2, components other than the cationic polymerization initiator may be used.
[0082] Examples of other components include solvents, ultraviolet absorbers, surfactants, polymerization inhibitors, antioxidants, coating film conditioners, light stabilizers, antioxidants, anti-coloring agents, dyes, fillers, and internal mold release agents.
[0083] Examples of the solvent include the solvents described in the above step 1.
[0084] Examples of the ultraviolet absorber include a hydroxyphenyltriazine ultraviolet absorber having a structure in which three hydrogen atoms on a triazine ring are substituted with phenyl groups, and a benzotriazole ultraviolet absorber having a benzotriazole structure.
[0085] In addition, examples of the surfactant include polyether-modified polysiloxane-based surfactants having a polyether structure.
[0086] (Steps of process 2)
[0087] In the step 2, the mixture obtained in the step 1 is mixed with a cationic polymerization initiator to produce a composition.
[0088] The method for mixing the mixture with the cationic polymerization initiator is not particularly limited, and the cationic polymerization initiator may be added to the mixture in portions or all at once.
[0089] During the mixing, stirring treatment may be performed as necessary.
[0090] The amount of the cationic polymerization initiator used is not particularly limited, but is preferably 0.1 to 2.0% by mass, more preferably 0.5 to 1.0% by mass, based on the total amount of the specific silsesquioxane used in step 1 and the metal oxide particles used in step 1, as described below.
[0091] In the method for producing the composition of the present embodiment, the amount of the metal oxide particles used in step 1 is not particularly limited, but is preferably 40 to 60% by mass, more preferably greater than 40% by mass and less than 60% by mass, relative to the total amount of the specific silsesquioxane used in step 1, the amount of the metal oxide particles used in step 1, and the amount of the cationic polymerization initiator used in step 2.
[0092] <Other Process>
[0093] The method for producing the composition of the present embodiment may include other steps in addition to step 1 and step 2.
[0094] As another step, when the mixture obtained in step 1 contains a solvent, step 3 of replacing the solvent in the mixture with another solvent may be performed between step 1 and step 2.
[0095] The steps of step 3 are not particularly limited, and for example, the following method can be cited: the first solvent contained in the mixture obtained in step 1 is volatilized and removed, and a second solvent of a different type from the volatilized first solvent is added to the obtained mixture. Alternatively, the following method can be used: after a second solvent of a different type from the first solvent contained in the mixture obtained in step 1 is added to the mixture, the first solvent is volatilized and removed from the obtained mixture.
[0096] The method for volatilizing the solvent is not particularly limited, and an example thereof includes a method of volatilizing the solvent by setting a reduced pressure condition.
[0097] The solvent (the above-mentioned other solvent) used in step 3 is not particularly limited, and examples thereof include the solvents described in the above-mentioned step 1. Among them, methanol, butyl cellosolve or methyl ethyl ketone is preferred.
[0098] [Composition]
[0099] Since the composition produced by the method for producing a composition according to the present embodiment contains a cationic polymerization initiator, it can be used as a curable composition.
[0100] The composition contains the above-mentioned specific silsesquioxane and metal oxide particles. In addition, as described above, it is estimated that the composition contains a prepolymerized specific silsesquioxane.
[0101] The content of the specific silsesquioxane in the composition of the present embodiment is not particularly limited, but is preferably 35 to 70% by mass, more preferably 35 to 60% by mass, relative to the total solid content in the composition of the present embodiment, from the viewpoint that the scratch hardness of a cured film formed using the composition is better and the viscosity of the composition changes less with time.
[0102] It should be noted that the solid content in the composition refers to the components constituting the cured film formed using the above composition, which corresponds to the above-mentioned specific silsesquioxane, metal oxide particles and thermal cationic polymerization initiator, etc., and the solvent is not included in the solid content. In addition, even if the component is in a liquid state, if it is a component constituting the cured film, it is also calculated as the solid content.
[0103] The content of the metal oxide particles in the composition of the present embodiment is not particularly limited, but is preferably 35 to 70% by mass, more preferably 35 to 60% by mass, relative to the total solid content in the composition of the present embodiment, from the viewpoint that the scratch hardness of a cured film formed using the composition is better and the viscosity of the composition changes less with time.
[0104] The content of the cationic polymerization initiator in the composition of the present embodiment is not particularly limited, but is preferably 0.1 to 3.0% by mass, more preferably 0.2 to 1.5% by mass, relative to the total solid content in the composition of the present embodiment, from the viewpoint that the scratch hardness of a cured film formed using the composition is better and the viscosity of the composition changes less with time.
[0105] When the composition of the present embodiment contains a UV absorber, the content of the UV absorber is not particularly limited, but is preferably 0.1 to 10% by mass, more preferably 0.5 to 2.0% by mass, based on the total solid content in the composition of the present embodiment.
[0106] When the composition of the present embodiment contains a surfactant, the content of the surfactant is not particularly limited, but is preferably 0.1 to 10% by mass, more preferably 0.5 to 2.0% by mass, based on the total solid content in the composition of the present embodiment.
[0107] The viscosity (20°C) of the composition is not particularly limited, but is preferably 60.0 cP or less, more preferably 30.0 cP or less, and further preferably 20.0 cP or less, from the perspective of obtaining a better scratch hardness of a cured film formed using the composition or better workability when forming the hard coating layer. The lower limit is not particularly limited, but is often 5.0 cP or more, and even more often 10.0 cP or more.
[0108] The above-mentioned viscosity can be measured using a known measuring device (for example, a cone-plate viscometer).
[0109] The solid content concentration of the composition is not particularly limited, but is preferably 40 to 70% by mass, more preferably 50 to 60% by mass, based on the total mass of the composition.
[0110] The above composition can be used as a composition for forming a cured film on a spectacle lens substrate, for example.
[0111] [Method for manufacturing eyeglass lenses]
[0112] The present disclosure also includes a method for producing an eyeglass lens, comprising the step of forming a cured film on an eyeglass lens substrate using the composition produced by the method for producing a composition according to the present embodiment.
[0113] Hereinafter, first, the materials and members used in this process are described in detail, and then the steps of the process are described in detail.
[0114] The composition used in this step is as described above.
[0115] Examples of the type of the eyeglass lens substrate used in this step include eyeglass lens substrates made of organic materials or inorganic materials.
[0116] Examples of eyeglass lens substrates include finished lenses whose convex and concave surfaces are optically polished and shaped according to a desired diopter, semi-finished lenses whose convex surfaces alone are polished into optical surfaces (e.g., spherical surfaces, rotationally aspherical surfaces, and progressive surfaces, etc.), and semi-finished lenses whose concave surfaces are processed and ground according to the wearer's prescription.
[0117] Examples of organic materials (so-called resins) include (meth)acrylic resins, thiourethane resins, allyl resins, episulfide resins, polycarbonate resins, polyurethane resins, polyester resins, polystyrene resins, polyethersulfone resins, poly-4-methyl-1-pentene resins, and diethylene glycol bisallyl carbonate resins (CR-39).
[0118] As an inorganic material, glass is mentioned, for example.
[0119] A primer layer may be disposed on the ophthalmic lens substrate.
[0120] From the perspective of workability, the thickness of the spectacle lens substrate may be 1 to 30 mm.
[0121] The thickness (average thickness) can be determined, for example, by measuring the thickness at five arbitrary points and taking the arithmetic average of the thicknesses.
[0122] The spectacle lens substrate preferably has light transmittance, and may be transparent or opaque. In addition, it may be colored.
[0123] (Steps of the process)
[0124] The method of forming a cured film on a lens substrate using the composition is not particularly limited, and examples thereof include a method of contacting the lens substrate with the composition to form a coating film on the lens substrate, and curing the coating film to form a cured film.
[0125] The steps of the above method are described in detail below.
[0126] The method of bringing the ophthalmic lens substrate into contact with the composition is not particularly limited, and the composition may be applied to the ophthalmic lens substrate or the ophthalmic lens substrate may be immersed in the composition.
[0127] The curing treatment step is not particularly limited, but heating treatment is preferred.
[0128] The conditions for the heat treatment are not particularly limited, and the optimal conditions are selected according to the type of thermal cationic polymerization initiator used. Among them, the heating temperature is preferably 30 to 120° C., more preferably 50 to 100° C., and the heating time is preferably 5 to 360 minutes, more preferably 10 to 60 minutes.
[0129] The thickness of the cured film is not particularly limited, and can be, for example, 1.0 μm or more, preferably 5.0 μm or more. The upper limit of the thickness can be, for example, 30.0 μm or less, preferably 20.0 μm or less.
[0130] The above film thickness is an average film thickness, and as a measuring method, the film thickness of the cured film is measured at 5 arbitrary points and the arithmetic average is calculated. Alternatively, an optical film thickness meter may be used.
[0131] Example
[0132] Hereinafter, the composition of the present disclosure will be described in more detail by way of examples and comparative examples, but the composition is not limited to these examples in any way.
[0133] <Example 1>
[0134] (Preparation of Composition (Step 1))
[0135] The composition of Example 1 was prepared by the following steps.
[0136] In a glass container equipped with a stirrer, a cationic curable silsesquioxane (manufactured by Toagosei Co., Ltd.: OX-SQ TX-100) (27.13 g) as the silsesquioxane (A) and colloidal silica (manufactured by JGC Catalysts & Chemicals Co., Ltd.: OSCAL-1432E, isopropyl alcohol dispersion, solid content 30% by mass) (90.45 g) as the metal oxide particles (B) were added to prepare a mixture.
[0137] The obtained mixture was stirred for 6 hours while being heated on a hot plate set at 160° C. At this time, the glass container was in a sealed state with a lid, and the solvent in the mixture was in a reflux state.
[0138] (Preparation of Composition (Step 3))
[0139] After the heating was completed, the obtained reaction solution was cooled to room temperature overnight, and butyl cellosolve (10.85 g) was added as a membrane forming solvent to the cooled reaction solution. Then, isopropyl alcohol was distilled off from the reaction solution under reduced pressure at 40° C. over 2 hours.
[0140] Methanol (33.40 g) was added to the obtained crude product to obtain a liquid composition X1.
[0141] (Preparation of Composition (Step 2))
[0142] In a glass container equipped with a stirrer, the liquid composition X1 (98.52 g) obtained in step 1 and SbF6 as a cationic polymerization initiator (D) were added. -A sulfonium salt (manufactured by Sanshin Chemical Industry Co., Ltd.: SAN-AID SI-150L) (0.52 g), a hydroxyphenyltriazine-based ultraviolet absorber (manufactured by BASF Japan: Tinuvin 477) (0.62 g) as a ultraviolet absorber (F) and a polyether-modified polysiloxane (manufactured by Dow Corning Toray Co., Ltd.: DOWSIL L-7001) (0.33 g) as a surfactant (G) were mixed to obtain a composition 1.
[0143] <Examples 2, 5 to 9, Comparative Examples 2 to 3>
[0144] Compositions 2, 5 to 9 and compositions C2 to C3 were obtained in the same manner as in Example 1 except that the set temperature of the hot plate and the heating time were changed to the values shown in Table 1 when the mixture was heated.
[0145] In addition, Comparative Example 2 corresponds to an example in which the heat treatment in Step 1 was not performed.
[0146] <Example 3>
[0147] Composition 3 was obtained by following the same procedures as in Example 1, except that the amount of cationic curable silsesquioxane (manufactured by Toagosei Co., Ltd.: OX-SQ TX-100) used was changed from 27.13 g to 32.56 g, and the amount of colloidal silica (manufactured by JGC Catalysts & Chemicals Co., Ltd.: OSCAL-1432E, isopropyl alcohol dispersion, solid content 30% by mass) used was changed from 90.45 g to 72.36 g.
[0148] <Example 4>
[0149] Composition 4 was obtained by following the same procedures as in Example 1, except that the amount of cationic curable silsesquioxane (manufactured by Toagosei Co., Ltd.: OX-SQ TX-100) used was changed from 27.13 g to 21.71 g, and the amount of colloidal silica (manufactured by JGC Catalysts & Chemicals Co., Ltd.: OSCAL-1432E, isopropyl alcohol dispersion, solid content 30% by mass) used was changed from 90.45 g to 108.7 g.
[0150] <Comparative Example 1>
[0151] 3-Glycidyloxypropyltrimethoxysilane (KBM403 manufactured by Shin-Etsu Chemical Co., Ltd.) (19.70 g) as the (C) hydrolyzable silicon compound was added to a glass container equipped with a stirrer, and 0.1 N hydrochloric acid (4.50 g) was slowly added dropwise while stirring the mixture.
[0152] After completion of the dropwise addition, the mixture was stirred at room temperature for 24 hours.
[0153] Next, titanium oxide colloid (manufactured by Nichiei Shokubai Kasei Co., Ltd.: NE58, solid content 30% by mass) (35.60 g) as the (B) metal oxide particles, aluminum acetylacetonate (manufactured by KISHIDA CHEMICAL CO., LTD.) (1.60 g) as the (E) catalyst, methanol (38.50 g), and polyether-modified polysiloxane (manufactured by Toray Dow Corning Co., Ltd.: DOWSIL L-7001) (0.10 g) as the (G) surfactant were added to the obtained mixture and mixed to obtain Composition C1 of Comparative Example 1.
[0154] <Evaluation>
[0155] Using the compositions obtained in the above Examples and Comparative Examples, the following evaluations were carried out. It should be noted that the results are summarized in Table 1 described later.
[0156] (Viscosity stability over time)
[0157] For the compositions of each Example or Comparative Example, the viscosity stability over time was measured by the following method.
[0158] Before the standing treatment described later, the temperature of the composition was adjusted to 20 °C, and the initial viscosity of the composition was measured using a vibrating viscometer (manufactured by Yamakichi Electric Co., Ltd.: VM-100).
[0159] After the above initial viscosity measurement, the composition was allowed to stand for 24 hours at 5 °C under light-shielded conditions, and then the viscosity of the composition after the standing treatment was measured in the same manner as the above initial viscosity measurement as the viscosity over time.
[0160] Based on the values of the above initial viscosity and the viscosity over time, the viscosity change rate over time was calculated as follows, and the viscosity stability over time was evaluated based on the following evaluation criteria.
[0161] Viscosity change rate over time (%) = 100 × (|(viscosity over time) - (initial viscosity)| / (initial viscosity))
[0162] (Evaluation criteria for viscosity stability over time)
[0163] A: Viscosity change rate over time is 10% or less
[0164] B: Viscosity change rate over time is greater than 10% and 50% or less
[0165] C: Viscosity change rate over time is greater than 50% and 200% or less
[0166] D: Viscosity change rate over time is greater than 200%
[0167] (Evaluation of pencil hardness)
[0168] Using the composition of each example or comparative example, a plastic eyeglass lens substrate with a cured film was produced by the following method.
[0169] First, as a plastic eyeglass lens substrate, a lens having a refractive index of 1.60 (manufactured by Nikon Essilor Co., Ltd.: Nikon Lite AS blank S-3.00D) was used.
[0170] The composition of each example or comparative example was applied to one surface of the plastic lens substrate by spin coating. Specifically, the plastic lens substrate was rotated at 300 rpm for 1 second, 4 ml of the composition was dripped from the center to the periphery of the plastic lens substrate during the rotation, and then the plastic lens substrate coated with the composition was further rotated at 300 rpm for 15 seconds, further rotated at 400 rpm for 5 seconds and then rotated for 1 second, further rotated at 700 rpm for 5 seconds and then rotated for 1 second, and further rotated at 2000 rpm for 9.9 seconds and then rotated for 1 second to obtain a plastic lens substrate with a coating.
[0171] Next, the obtained plastic eyeglass lens substrate with a coating film was heated at 100° C. for 20 minutes and then further heated at 100° C. for 1 hour to form a cured film, thereby obtaining a plastic eyeglass lens substrate with a cured film. The obtained cured film had a thickness of 15 μm.
[0172] The scratch hardness (pencil hardness) was evaluated by the following procedure using the plastic eyeglass lens substrate with a cured film produced using the composition of each Example or Comparative Example.
[0173] Specifically, the pencil hardness of the cured film was measured according to the method specified in JIS K5600-5-4 (1999), and evaluated based on the following evaluation criteria.
[0174] A: Pencil hardness is 4H or above
[0175] B: Pencil hardness is 3H or more and less than 4H
[0176] C: Pencil hardness is 2H or more and less than 3H
[0177] (Evaluation of scratch hardness)
[0178] A plastic eyeglass lens substrate with a cured film was produced by the method described in (Evaluation of Pencil Hardness) using the composition of each Example or Comparative Example.
[0179] The obtained plastic eyeglass lens substrate with a cured film was used to evaluate the scratch hardness by the following procedure.
[0180] Using a friction and wear tester (manufactured by Shinto Scientific Co., Ltd.: Tribo Gear TYPE40), a sapphire scraper needle (manufactured by Shinto Scientific Co., Ltd.: BH0001-02) with a tip radius of 0.01 mm and a top angle of 60° was brought into vertical contact with the convex surface (surface with a cured film) of the plastic eyeglass lens substrate with a cured film produced by the above steps. While applying a vertical load of 10 g to the scraper needle, it was moved 10 mm at a time at a speed of 60 mm / min.
[0181] The depth of the scratch marks on the convex surface of the plastic eyeglass lens substrate with the cured film was measured using a scanning white interference microscope (VS1000 manufactured by Hitachi, Ltd.), and the scratch hardness was evaluated based on the following evaluation criteria.
[0182] A: The depth of the scratch is less than 50nm
[0183] B: The depth of the scratch is greater than 50nm and less than 80nm
[0184] C: The depth of the scratch is greater than 80nm
[0185] Table 1 shows the evaluation results.
[0186] The description of each numerical value shown in the table represents the usage-amount (mass parts) of each component in the composition.
[0187] In the table, the column "B / A+B+D (mass %)" shows the amount of the (B) metal oxide particles used relative to the total amount of the (A) silsesquioxane used, the (B) metal oxide particles used, and the (D) cationic polymerization initiator used in the production method of the present disclosure (unit: mass %).
[0188] In the table, the column "Heating temperature" indicates the set temperature of the hot plate when the mixture is heated in the above step 1.
[0189] In the table, the column "Heating time" indicates the heating time (stirring time) when the mixture is heated in the above step 1.
[0190] In the table, the column "Film Thickness" indicates the film thickness of the cured film. The above film thickness is a value measured using an optical film thickness meter.
[0191] In the table, the column "Hardness-1" shows the result of the above (Evaluation of pencil hardness), the column "Hardness-2" shows the result of the above (Evaluation of scratch hardness), and the column "Viscosity" shows the result of the above (Temporal viscosity stability).
[0192]
[0193] As shown in Table 1, it was confirmed that the composition of the present disclosure exhibited the desired effects.
Claims
1. A method for producing a composition, comprising: Step 1 of heating a mixture containing silsesquioxane having a cationically polymerizable group and metal oxide particles at a temperature exceeding 60° C.; and Step 2 is to mix the mixture obtained in the step 1 with a cationic polymerization initiator to produce a composition.
2. The method for producing a composition according to claim 1, wherein The heating time is more than 1 hour.
3. The method for producing a composition according to claim 1 or 2, wherein: The heating temperature is above 100°C.
4. The method for producing a composition according to any one of claims 1 to 3, wherein The amount of the metal oxide particles used is 40 to 60% by mass based on the total amount of the silsesquioxane having a cationically polymerizable group, the metal oxide particles, and the cationic polymerization initiator used.
5. The method for producing a composition according to any one of claims 1 to 4, wherein The metal oxide particles contain at least one atom selected from the group consisting of Si, Sn, Zr, and Ti.
6. The method for producing a composition according to any one of claims 1 to 5, wherein The cationically polymerizable group is an oxetanyl group. 7 . A method for producing an eyeglass lens, comprising the step of forming a cured film on an eyeglass lens substrate using the composition produced by the production method according to claim 1 .
Citation Information
Patent Citations
Hard coat composition
JP2010515778A